1969
DOI: 10.12669/pjms.324.10290
|View full text |Cite
|
Sign up to set email alerts
|

A New Formula for Non-invasive Assessment of Intravascular Fluid Status with Inferior Vena Cava Diameters and Collapsibility Index: A Pilot Study

Abstract: Objective:To evaluate the correlation between central venous pressure (CVP) and inferior vena cava (IVC) diameters measured by ultrasonography (Ultrasound) in critically ill patients.Methods:Intubated critically ill patients were enrolled. The CVP values were measured using a U-tube manometer and were compared to the IVC diameters and collapsibility index, which were measured by bedside Ultrasound. Patients younger than 18 years old, who were not intubated, who had an abdominal pressure greater than 12 mmHg, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…IVCCI is a simple predictor of volume responsiveness both in mechanically ventilated and spontaneously breathing patients. [12131415] An observational study reported that IVCCI >42% has 97% specificity and 90% positive predictive value for fluid responsiveness spontaneously breathing adult patients. [12] Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…IVCCI is a simple predictor of volume responsiveness both in mechanically ventilated and spontaneously breathing patients. [12131415] An observational study reported that IVCCI >42% has 97% specificity and 90% positive predictive value for fluid responsiveness spontaneously breathing adult patients. [12] Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, a similar problem exists in determining intravascular volume status in critical patients . Recent studies have identified numerous deficiencies with the current methods used to estimate fluid status, including heart rate, blood pressure, physical examination findings, and laboratory findings .…”
mentioning
confidence: 99%
“…[1,21] Much research has focused on the elasticity of large veins, such as the inferior vena cava and the internal jugular vein, to calculate standardized parameters for the determination of fluid responsiveness, including the collapsibility index. [2,[22][23][24] These parameters are related to more traditional predictors of fluid responsiveness like central venous pressure. Emerging studies, however, demonstrate that large arteries, such as the common carotid artery, are also dynamically compliant, and can predict fl uid responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A study in 2016 by Karacabey et al [2] revealed that measures of IVC collapsibility were inversely correlated with CVP measurements in intubated patients. If the diameter of the IVC is less than 2.1 cm and decreases by more than half during inhalation, then the right atrial pressure sits within the normal range of 0-5 mmHg.…”
Section: Understanding Measurement Of Ivc (Diameter Collapsibility mentioning
confidence: 99%
See 1 more Smart Citation